2010
DOI: 10.1111/j.1423-0410.2009.01235.x
|View full text |Cite
|
Sign up to set email alerts
|

TRALI is due to pulmonary venule damage from leucocytes with cholesterol crystal formation

Abstract: Pulmonary damage in TRALI is related to formation of cholesterol crystals that appear to pierce endothelial membranes of venules. The endothelial defects lead to plasma extravasation into the alveoli causing TRALI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…33 In another series of 3 fatal cases of immune-mediated TRALI, the autopsy demonstrated pulmonary edema with cholesterol crystals in the endothelial membranes of venules. 34 In this series, patient 1 had HLA class I A2 antigen corresponding to the donor's antibodies; in case 2, no WBC antibodies were identified in the donor, and in case 3 the donor had antibodies to HNA-3a. The proposed pathogenesis based on these findings is that WBCs are coated with antibodies then attached to the pulmonary venule endothelium where WBCs are activated.…”
Section: Incidence Outcome and Blood Component Associationmentioning
confidence: 99%
“…33 In another series of 3 fatal cases of immune-mediated TRALI, the autopsy demonstrated pulmonary edema with cholesterol crystals in the endothelial membranes of venules. 34 In this series, patient 1 had HLA class I A2 antigen corresponding to the donor's antibodies; in case 2, no WBC antibodies were identified in the donor, and in case 3 the donor had antibodies to HNA-3a. The proposed pathogenesis based on these findings is that WBCs are coated with antibodies then attached to the pulmonary venule endothelium where WBCs are activated.…”
Section: Incidence Outcome and Blood Component Associationmentioning
confidence: 99%
“…1 By SEM and GC-MS, we showed that intravascular, extracellular cholesterol crystals were associated with these endothelial tears to which the pulmonary edema was attributed. 1 We now report a new finding discovered by TEM: crystals within neutrophils.…”
Section: Discussionmentioning
confidence: 86%
“…1 By SEM and GC-MS, we showed that intravascular, extracellular cholesterol crystals were associated with these endothelial tears to which the pulmonary edema was attributed. 1 We now report a new finding discovered by TEM: crystals within neutrophils. Our modified hypothesis is that cholesterol crystals initially form within degranulated neutrophils, some crystals escape into the pulmonary capillaries, and the majority of crystals, in attached neutrophils, tear through the postcapillary venules with extravasation of plasma, causing the clinical condition known as TRALI.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…For example, two recent studies reported that cholesterol crystal accumulation in neutrophils, and secondarily, in endothelial cells, may underlie the pathogenesis of transfusion-related acute lung injury [43]. …”
Section: Cholesterol Impacts Neutrophil Functionmentioning
confidence: 99%